Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1029/2019ea001018
|View full text |Cite
|
Sign up to set email alerts
|

Altitude Aerosol Measurements in Central France: Seasonality, Sources and Free‐Troposphere/Boundary Layer Segregation

Abstract: Long-term and continuous measurements of aerosol chemical composition is essential to improve our understanding of the formation and transformation of aerosol particles in the atmosphere. Thanks to the recent developments of aerosol mass spectrometry, notably with the Aerosol Chemical Speciation Monitor (ACSM, Aerodyne; Fröhlich et al., 2013; Ng et al., 2011), this information can be acquired over long periods of time with minimal intervention from the user. The ACSM is a robust tool that measures aerosol chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 96 publications
0
1
0
Order By: Relevance
“…Furthermore, the seasonal trend in aerosol properties at PUY has previously been reported for aerosol concentrations by Farah et al. (2021), Bourcier et al. (2012), and Venzac et al.…”
Section: General Observations and Time Seriessupporting
confidence: 60%
See 1 more Smart Citation
“…Furthermore, the seasonal trend in aerosol properties at PUY has previously been reported for aerosol concentrations by Farah et al. (2021), Bourcier et al. (2012), and Venzac et al.…”
Section: General Observations and Time Seriessupporting
confidence: 60%
“…INPs of marine origin are suspected to play an important role in cloud formation in the remote ocean environment (DeMott et al, 2016;McCluskey et al, 2018;Wilson et al, 2015), but have never been shown to be important in continental areas where terrestrial sources are considered a major contribution (Burrows et al, 2013;Huang et al, 2021). Atlantic air masses represent about 40%-50% of the air masses during the autumn and winter at PUY (Farah et al, 2018(Farah et al, , 2021.…”
Section: Grouped Inp Datamentioning
confidence: 99%
“…Furthermore, SOA (LO-OOA and MO-OOA) was dominant (approximately 90%) in OA, consistent with other regional studies. 42,43 The mass fraction of MO-OOA (f MO-OOA ) in cloud residual and cloud interstitial particles increased when the cloud events occurred (Figure 1) ,and it also increased with the duration of the cloud event, which might suggest clouds could promote MO-OOA formation through oxidation, especially in the cloud residuals. Notably, higher f MO-OOA values during CE4 and CE5 than during other events (i.e., CE1, CE2, and CE3) were likely attributed to more LO-OOA being further oxidized in those cloud events.…”
Section: ■ Results and Discussionmentioning
confidence: 99%